Evaluation of a Virtual Reality Platform to Train Stress Management Skills for a Defense Workforce: Multisite, Mixed Methods Feasibility Study - Murielle G Kluge; Steven Maltby; Caroline Kuhne; Nicole Walker; Neanne Bennett; Eugene Aidman; Eugene Nalivaiko; Frederick Rohan Walker (JMIR Publications, 2023)
BackgroundPsychological stress-related injuries within first-responder organizations have created a need for the implementation of effective stress management training. Most stress management training solutions have limitations associated with scaled adoption within the workforce. For instance, those that are effective in civilian populations often do not align with the human performance culture embedded within first-responder organizations. Programs involving expert-led instructions that are high in quality are often expensive. ObjectiveThis study sought to evaluate a tailored stress management training platform within the existing training schedule of the Australian Defense Force (ADF). The platform, known as Performance Edge (PE), is a novel virtual reality (VR) and biofeedback-enabled stress management skills training platform. Focusing on practical training of well-established skills and strategies, the platform was designed to take advantage of VR technology to generate an immersive and private training environment. This study aimed to assess the feasibility of delivering the VR platform within the existing group-based training context and intended training population. In this setting, the study further aimed to collect data on critical predictors of user acceptance and technology adoption in education, including perceived usability, usefulness, and engagement, while also assessing training impacts. MethodsThis study used a mixed methods, multisite approach to collect observational, self-reported, and biometric data from both training staff and trainers within a real-world "on-base" training context in the ADF. Validated scales include the Presence Questionnaire and User Engagement Scale for perceived usefulness, usability, and engagement, as well as the State Mindfulness Scale and Relaxation Inventory, to gain insights into immediate training impacts for specific training modules. Additional surveys were specifically developed to assess implementation feedback, intention to use skills, and perceived training impact and value. ResultsPE training was delivered to 189 ADF trainees over 372 training sessions. The platform was easy to use at an individual level and was feasible to deliver in a classroom setting. Trainee feedback consistently showed high levels of engagement and a sense of presence with the training content and environment. PE is overall perceived as an effective and useful training tool. Self-report and objective indices confirmed knowledge improvement, increased skill confidence, and increased competency after training. Specific training elements resulted in increased state mindfulness, increased physical relaxation, and reduced breathing rate. The ability to practice cognitive strategies in a diverse, private, and immersive training environment while in a group setting was highlighted as particularly valuable. ConclusionsThis study found the VR-based platform (PE) to be a feasible stress management training solution for group-based training delivery in a defense population. Furthermore, the intended end users, both trainers and trainees, perceive the platform to be usable, useful, engaging, and effective for training, suggesting end-user acceptance and potential for technology adoption.